Lobectomy on ECMO as a Life-Saving Procedure following Necrotizing Pneumonia in a Toddler: A Case Study - Ashkenazi, Shira; Ben-Nun, Alon; Pessach, Itai; Rubinshtein, Marina; Paret, Gideon (Journal of Pediatric Intensive Care, 2018)
Necrotizing pneumonia is a severe form of pneumonia that is mainly treated with conservative treatment, including antibiotics. We report a unique case of necrotizing pneumonia due to group A streptococcus infection in an 18-month-old boy who required extracorporeal membrane oxygenation (ECMO) support. Following surgical lobectomy, the child was weaned off ECMO and recovered uneventfully.
Keywords: necrotizing pneumonia; ECMO; lobectomy